Einstein y el arte de montar en bicicleta : buscando el equilibrio en el mundo moderno - Irvine, Ben, 1979- (Tiempo de mirar ;, 2016)
Einstein and the Art of Mindful Cycling shines new light onto one of the great scientific icons, and explores how pushing that pedal can nurture mindfulness in a spiritually stressful age. The author steers us through his own perspective on cycling - weaving the philosophical, practical and personal into an elegant balance. Add in a sprinkling of meditative insights, and we can all learn how to experience Einstein's enlightened outlook on life through the simple joy of riding a bicycle.